Using newspapers to reinforce foreign language skills - Farquhar, Bernadette (School of Languages, NIHERST, 1992)
This paper demonstrates, through the use of France-Antilles, a French West Indian daily newspaper, that the language teacher can devise activities and exercises that provide grammar practice without the abstract mechanical quality of drills done in isolation
Keywords: Foreign language education